2008
DOI: 10.1142/s0192415x08006466
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater Clam Extract Ameliorates Acute Liver Injury Induced by Hemorrhage in Rats

Abstract: The freshwater clam is a widely-consumed shellfish and is used as a remedy for chronic hepatitis in Asia. However, its contribution to acute liver injury (ALI) remains unclear. The aim of this study is to assess the protective effects of freshwater clam extract (CE) in ALI induced by hemorrhage in rats. Rats were randomly divided into 5 groups, (1) blood loss (BL) 40%, (2) CE 150 mg/kg plus BL 40%, (3) CE 75 mg/kg plus BL 40%, (4) CE 150 mg/kg, and (5) CE 75 mg/kg groups. CE was given by femoral vein catheter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 29 publications
2
36
0
Order By: Relevance
“…Studies have shown that freshwater clams have protective properties against liver injury induced D-galactosamine, 11) hemorrhage, 12) and CCl 4 13) in rats. In this study, we examined whether FCE and fat/protein fractions of FCE exerted hepatoprotective effects Table 2.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have shown that freshwater clams have protective properties against liver injury induced D-galactosamine, 11) hemorrhage, 12) and CCl 4 13) in rats. In this study, we examined whether FCE and fat/protein fractions of FCE exerted hepatoprotective effects Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…30) FCE administration ameliorates liver damage by suppressing the production of tumor necrosis factor (TNF)-α, which is induced by hemorrhage. 12) However, more investigations are required to ascertain if FCE and its fractions suppress TNF-α production in rats exposed to xenobiotics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…WEC contains high levels of free amino acids, glycogen, vitamins, and mineral substances which mediate many physiological functions (Peng et al, 2008;Watanabe et al, 2001;Wohlt et al, 1994). Previous studies have shown that WEC has beneficial effects such as reducing fatty acid and cholesterol synthesis, thus helping to prevent cardiovascular diseases (Childs et al, 1990;Iritani et al, 1979).…”
Section: Introductionmentioning
confidence: 99%